Dermoscopy of Hair and Scalp Disorders (Trichoscopy) in Skin of Color—A Systematic Review by the International Dermoscopy Society “Imaging in Skin of Color” Task Force - Khare, Soumil; Behera, Biswanath; Ding, Delaney D; Lallas, Aimilios; Chauhan, Payal; Enechukwu, Nkechi Anne; Sławińska, Martyna; Akay, Bengu Nisa; Ankad, Balachandra S; Bhat, Yasmeen J; Jha, Abhijeet Kumar; Kaliyadan, Feroze; et al. (Dermatology Practical & Conceptual, 2023)
Hair and scalp disorders are of significant interest for physicians dealing with dark phototypes due to their prevalence and potential aesthetic impact resulting from a higher tendency for scarring. In order to facilitate their non-invasive diagnosis, several dermoscopic studies have been published, yet data are sparse and no systematic analysis of the literature has been performed so far. This systematic literature review summarizes published data on trichoscopy of hair and scalp diseases (trichoscopic findings, used setting, pathological correlation, and level of evidence of studies). A total of 60 papers addressing 19 different disorders (eight non-cicatricial alopecias, nine cicatricial alopecias, and two hair shaft disorders) were assessed, for a total of 2636 instances. They included one cross-sectional analysis, 20 case-control studies, 25 case-series, and 14 single case-reports, so the level of evidence was V and IV in 65% and 33% of cases, respectively, with only one study showing a level of evidence of III. Notably, although there is a considerable body of literature on trichoscopy of hair/scalp diseases, our review underlined that potentially significant variables (e.g., disease stage or hair texture) are often not taken into account in published analyses, with possible biases on trichoscopic patterns, especially when it comes to hair shaft changes. Further analyses considering all such issues are therefore needed.